Faktor-Faktor Pembentuk Komitmen Profesional Siswa Seminari Menengah St. Vincentus A Paulo Blitar - Yuniarto, Antonius (Universitas Dr. Soetomo, 2019)
Abstract This research aims to examine and analyze the influence of Motivation, Transformational Leadership and Service Quality towards Satisfaction and Professional Commitment of Minor Seminary’ Students of St. Vincentius A Paulo at Blitar. The population of this research is Minor Seminary’ Students of St. Vincentius A Paulo at Blitar. The research sampling method used census method. The instrument of this research was questioners. The data were collected from the questioners which were distributed to 115 students at Minor Seminary of St. Vincentius A Paulo at Blitar, tested by Structural Equation Modelling (SEM). Motivation measured by three indicators (ERG theory) which introduced by Alderfer (Gibson et al., 2006:94). Transformational Leadership measured by four indicators which introduced by Robin and Judge (2011: 391). Service Quality based on Lovelock & Wright (2002: 266: 267); Satisfaction based on Westbrook and Oliver (1991); Professional Commitment based on Kalbers and Fogarty (1995).In measuring the data, this research used Likert Scale, while in measuring the validity and reliability, this research was used validity and reliability test based on Crombach’s Alpha to the internal consistence by using SPSS program version 22 with Analysis of Moment Structure (AMOS) version 23. The model of relationship between the variables studied shown that Motivation, Transformational Leadership and Service Quality have significant influence to Satisfaction and Professional Commitment of Minor Seminary’ Students of St. Vincentius A Paulo at Blitar.Based on the result of this research, Rector of Minor Seminary of St. Vincentius A Paulo at Blitar suggested to give comprehensive attention to the variables that influenced Professional Commitment: Motivation, Transformational Leadership, Service Quality, Satisfaction of Minor Seminary’ Students of St. Vincentius A Paulo at Blitar.